The Method of Organizing Students' Activities in Physical Education Classes at School - Safarov Chingizkhan Bakhtiyarovich (Scientific Trends, 2025)
Physical education classes are an important tool for the formation of a healthy lifestyle of students, their physical development and the development of movement skills. Effective organization of these lessons and ensuring active participation of students requires pedagogical skills and methodical approaches. This article describes the methods of effective organization of students' activities in physical education classes.
Keywords: Effective organization of physical education classes plays an important role in the healthy and active growth of students.